Acceptance of disease and coping with pain as essentials components of quality with life in patients with migraine. Preliminary study - Rolka, Hanna; Krajewska-Kułak, Elżbieta; Kułak, Wojciech; Drozdowski, Wiesław; Gołębiewska, Agata; Kondzior, Dorota (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Migraine is disease characterized by headache attacks, nausea, vomits, vertigo, sensitivity to sound, light and smell. During migraine attack patients are not active in daily life. Aim. Assessment of disease acceptance and significant factors affected on social life in patients with diagnosed migraine. Assessment of more common coping strategies with pain by patients. Material and methods. In the study we used diagnostic survey. Authors questionnaire included Acceptance of Illness Scale (AIS) and Coping Strategies Questionnaire (CSQ). The study group included 60 active workers with migraine. In this group 39 patients (65%) had migraine with aura and 21 (35%) had migraine without aura. The patients had attacks with different severity of main and additional signs. Results. The greatest group of patients was migraine with aura in 65% of active workers aged 25-45 years. Almost 87% of patients had moderate severity migraine attacks, patients with severe and very severe migraine attacks took triptans. Nearly 26 (44%) patients obtained 30-40 scores in AIS which indicate high migraine acceptance, 23 (38%) patients obtained mild values in AIS. Most of patients use strategies which make creative life: copying with pain and revaluation of pain feelings. <br.=< Conclusions: 1. Heath status significantly affect or unable daily activity in patients with moderate, severe or very severe migraine attacks. 2. Most patients had high level of illness acceptance. 3. The patients use selected strategies of copying, revaluation of pain feelings during attacks.